Cyberbullying and its Impact in Indonesia: Legal Protection for Victims from The Perspective of The ITE Law and Cyber Law - Dikrurahman, Diky; Putra, Dwi Rayhan Sunandar (Politeknik Siber Cerdika Internasional, 2024)
Cyberbullying has become a significant social problem in Indonesia, especially among teenagers. With the increasing use of the internet and social media, cases of cyberbullying are increasingly being reported, causing negative impacts on victims, including psychological and social disorders. This study aims to explore the impact of cyberbullying in Indonesia and assess legal protection for victims in the context of the ITE Law and cyber law. The research method used is a qualitative approach with case study analysis, where data is collected through interviews with victims, parents, and legal experts, as well as analysis of relevant legal documents. The study found that many victims of cyberbullying experienced profound psychological impacts and felt less protected by existing regulations. Although the ITE Law provides a legal basis for dealing with cyberbullying, many cases are not followed up effectively. The need to increase public understanding regarding victims' rights and applicable legal provisions is one of the main recommendations.